Effectiveness of 13-valent pneumococcal conjugate vaccination for protection against acute otitis media caused by Streptococcus pneumoniae in healthy young children: a prospective observational study. (August 2018) - Pichichero, Michael; Kaur, Ravinder; Scott, Daniel A; Gruber, William C; Trammel, James; Almudevar, Anthony; Center, Kimberly J
Summary: Background: With wide use of the seven-valent pneumococcal conjugate vaccine (PCV7) for protection against acute otitis media caused by Streptococcus pneumoniae serotypes included in the vaccine, efficacy testing for the 13-valent vaccine (PCV13) was not feasible. We aimed to assess the effectiveness of PCV13 in preventing acute otitis media caused by the six serotypes in PCV13 that were not in PCV7. Methods: We did a longitudinal observational study in healthy children seen as outpatients in a private paediatric practice in Rochester, NY, USA. Children aged up to 30 months who had received the full primary series of PCV13 with other recommended vaccines were eligible to participate and were followed up to age 30–36 months to identify episodes of acute otitis media, during which we collected middle-ear fluid (MEF) by tympanocentesis. We assessed MEF for the serotypes common to PCV7 and PCV13 (4, 6B, 9V, 14, 18C, 19F, and 23F) and the six additional serotypes specific to PCV13 (1, 3, 5, 6A, 7F, and 19A). As controls, we included children enrolled in a longitudinal study in the study centre from Oct 1, 2007, to Sept 30, 2009, who had been vaccinated with PCV7, had MEF prospectively collected at the onset of acute otitis media, and been followed up until age 30 months. The primary outcome was the effectiveness of PCV13 to prevent acute otitis media caused by pneumococci expressing the six capsular serotypes not included in PCV7 (1, 3, 5, 6A, 7F, and 19A). This study is registered withClinicalTrials.gov, numberNCT01199016 . Findings: From Sept 28, 2010, to Sept 30, 2013, we enrolled 239 children (123 [51%] boys and 116 [49%] girls; median age 6·3 months [IQR 6·1–8·6]) in the PCV13 cohort, and 162 completed the study. Of 348 children (184 [53%] boys and 164 [47%] girls; 6·5 months [6·1–9·1]) included in the PCV7 cohort, 248 completed follow-up. 223 MEF samples were obtained at onset of acute otitis media from 90 children in the PCV13 cohort. 53 (24%) of 223 samples were culture positive for S pneumoniae, compared with 89 (31%) of 284 samples in the PCV7 cohort (p=0·06). Four (8%) of 53 samples in the PCV13 cohort contained pneumococci expressing one of the additional PCV13 capsular serotypes, compared with 46 (52%) of 89 samples in the PCV7 cohort, giving a relative reduction of 86% (95% CI 61–94, p=0·0010). The greatest reduction in MEF samples was in serotype 19A (two [4%] in the PCV13 cohort vs 46 [52%] in the PCV7 cohort; relative reduction 91% [58–97, p=0·0010]). Interpretation: PCV13 prevents acute otitis media caused by S pneumoniae expressing serotypes included in the vaccine. Funding: Pfizer.